Seberapa Penting Penggunaan Informasi Akuntansi melalui: Persepsi, Pelatihan, Pengetahuan dan Skala Usaha pada UMKM? - Putri, Anandita Zulia; Khotimah, Khusnul; Pramudiati, Ningrum (Universitas Muhammadiyah Metro, 2024)
TUsers of accounting information can become large capital in a company to carry out strategic planning, supervision in management and operational supervision. This study aims to empirically evaluate how owner perceptions, accounting training, accounting knowledge, and business scale influence how accounting information is used. Researchers are interested in conducting new studies because they continue to produce inconsistent results based on previous investigations. A survey using a questionnaire is the research methodology used. Purposive sampling is a technique used to select a sample. In this study, 150 food and beverage MSME owners in Purworejo Regency participated as respondents. SPSS statistical software version 26 was used to perform data analysis techniques. In this work, multiple linear regression analysis uses analytical tools. This study used multiple linear regression analysis as an analytical tool. The findings show a positive effect between the use of accounting information and the owner's perception, accounting training, accounting knowledge, and business scale. It is hoped that further research will guide researchers in filling out questionnaires, relevant agencies will carry out regular training and update MSME data.